1992
DOI: 10.1126/science.1439826
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Correlates of Massive Cortical Reorganization

Abstract: (198933. We thank S. Guerder for the Rachel T cell clone;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
2
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(133 citation statements)
references
References 3 publications
(4 reference statements)
5
120
2
2
Order By: Relevance
“…Of course, switching from one virtual machine to another involves different detailed physical processes when the machine runs, even if there is no re-wiring or replacement of physical components: the changes involve different sequences of operations in large numbers in the computer". Compelling evidence for this comes from the findings reported by Ramachandran et al [473,474] in which they show that despite dramatic changes in nonconscious brain anatomical topology (IPST in our interpretation), particular representations remain available to the consciousness and can still be experienced as sensations of pain or cold. We believe that this is so because the higher level spatial-temporal patterns (OMs in our interpretations) that comprise the OST level were still present in the brain.…”
Section: Mechanismsupporting
confidence: 49%
“…Of course, switching from one virtual machine to another involves different detailed physical processes when the machine runs, even if there is no re-wiring or replacement of physical components: the changes involve different sequences of operations in large numbers in the computer". Compelling evidence for this comes from the findings reported by Ramachandran et al [473,474] in which they show that despite dramatic changes in nonconscious brain anatomical topology (IPST in our interpretation), particular representations remain available to the consciousness and can still be experienced as sensations of pain or cold. We believe that this is so because the higher level spatial-temporal patterns (OMs in our interpretations) that comprise the OST level were still present in the brain.…”
Section: Mechanismsupporting
confidence: 49%
“…In addition, it was observed that after arm amputation in humans, tactile stimulation of either the trunk or the face ipsilateral to the amputation stump can lead to a point-to-point somatotopic referral of stimuli applied to specific locations on the skin to specific locations on the phantom limb. This phenomenon, termed 'remapping', has been claimed to be the perceptual correlate of cortical reorganization reported in the primate studies [5]. However, in contrast we had previously demonstrated cortical reorganization with magnetic source imaging that was independent of somatotopic remapping after amputation [7].…”
Section: Introductioncontrasting
confidence: 50%
“…This relationship was not significant for non-painful stimuli. To date, in most experiments concerning cortical reorganization after amputation or dorsal rhizotomy [1,2, 5,6,8], only unilateral effects in the primary somatosensory cortex contralateral to the lesion were studied. The bilaterality of the sites eliciting mislocalization in this study, however, cannot be explained solely on the basis of the generally known invasion of cortical projections from neighbouring areas into the 'amputation' zone.…”
mentioning
confidence: 99%
“…This is especially true given Body Beyond SI 9 the clear plasticity of somatotopic maps following peripheral trauma (Merzenich et al, 1984;Pons et al, 1991) and learning Pascual-Leone & Torres, 1993). While some referral of sensation between skin surfaces may occur following massive cortical reorganisation (e.g., Ramachandran, Rogers-Ramachandran, & Stewart, 1992) or in plasticity induced by simultaneous tactile co-activation of skin surfaces (Schweizer et al, 2001;Sterr et al, 1998), in most cases plastic changes in somatosensory cortex do not lead to mislocalsation of touch. For example, while mislocalisation of touch between fingers has been reported in three-finger Braille readers (Sterr et al, 1998), similar errors were not found for single-finger Braille readers (Sterr et al, 1998), who nevertheless show large plastic changes of somatosensory cortex (Pascual-Leone & Torres, 1993).…”
Section: Localisation Of Touch On the Body Surfacementioning
confidence: 99%